A Genome-Wide Association Study for Regulators of Micronucleus Formation in Mice - Rebecca E. McIntyre; Jérôme Nicod; Carla Daniela Robles-Espinoza; John Maciejowski; Na Cai; Jennifer Hill; Ruth Verstraten; Vivek Iyer; Alistair G. Rust; Gabriel Balmus; Richard Mott; Jonathan Flint; et al. (G3: Genes, Genomes, Genetics, 2016)
In mammals the regulation of genomic instability plays a key role in tumor suppression and also controls genome plasticity, which is important for recombination during the processes of immunity and meiosis. Most studies to identify regulators of genomic instability have been performed in cells in culture or in systems that report on gross rearrangements of the genome, yet subtle differences in the level of genomic instability can contribute to whole organism phenotypes such as tumor predisposition. Here we performed a genome-wide association study in a population of 1379 outbred Crl:CFW(SW)-US_P08 mice to dissect the genetic landscape of micronucleus formation, a biomarker of chromosomal breaks, whole chromosome loss, and extranuclear DNA. Variation in micronucleus levels is a complex trait with a genome-wide heritability of 53.1%. We identify seven loci influencing micronucleus formation (false discovery rate <5%), and define candidate genes at each locus. Intriguingly at several loci we find evidence for sexual dimorphism in micronucleus formation, with a locus on chromosome 11 being specific to males.